Diseño de una propuesta para ajustar la normatividad colombiana en cuanto a contaminación auditiva que se presenta en los autódromos en Colombia (2018)
Noise can be defined as a perception that if it is not pleasant is potentially harmful, effects and deteriorates the quality of life of people. The World Health Organization (WHO) has defined pollution as the third most important environmental problem in the world. The Ministry of Environment, Housing and Territorial Development developed Resolution 0627 of 2006, which refers to the national noise and environmental noise emission standard; This standard stipulates the permitted decibel levels classified by zones. With this research project it is expected that the XRP Motopark of Cajicá can adapt or seek a modification to the noise emission regulations in order to continue with its normal activities, without having cancellations of events, or sanctions for non-compliance with standards.